2019
DOI: 10.33747/stiesmg.v11i1.338
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Universitas Muria Kudus

Abstract: This study aims to examine the influence of Compensation, Work Motivation and Discipline to Performance Employee in Muria Kudus University.The research was conducted by using survey methods to Employees Administrative in Muria Kudus University and analyzed by using regression analysis. The samples in this study were taken 45 people with a view to facilitate researchers in conducting research. While sampling technique used in this study using purposive sampling technique in which the sample collection elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 1 publication
2
12
0
4
Order By: Relevance
“…The results of this statistical test indicate that the employee discipline variable affects the increase in employee performance by 0.640 units and discipline has a positive and significant effect on improving the performance of the employee. The existence of a positive and significant relationship between discipline and performance has been reported by several previous researchers, such as Bagis et al (2019), Burhannudin et al (2019), Shofwani & Hariyadi (2019), Angriani &Eliyana (2020), andYonata et al (2020) who reported that discipline has a positive and significant effect on employee performance. If employee discipline is improved, it will have high implications for improving employee performance.…”
Section: The Effect Of Discipline On Performancesupporting
confidence: 52%
See 3 more Smart Citations
“…The results of this statistical test indicate that the employee discipline variable affects the increase in employee performance by 0.640 units and discipline has a positive and significant effect on improving the performance of the employee. The existence of a positive and significant relationship between discipline and performance has been reported by several previous researchers, such as Bagis et al (2019), Burhannudin et al (2019), Shofwani & Hariyadi (2019), Angriani &Eliyana (2020), andYonata et al (2020) who reported that discipline has a positive and significant effect on employee performance. If employee discipline is improved, it will have high implications for improving employee performance.…”
Section: The Effect Of Discipline On Performancesupporting
confidence: 52%
“…Bagis et al (2019) dan Burhannudin, Zainul, & Harlie (2019) reported that there is a positive and significant relationship between work discipline and employee performance in educational institutions. Shofwani and Hariyadi (2019) reported the effect of work discipline on employee performance at Muri Kudus University with a t-count of 2,228 with sig. 0.031 < sig.…”
Section: The Effect Of Discipline On Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The provision of compensation to employees in accordance with employee performance encourages employees to improve their competence. According to (Cahyani, 2020), (Siagian & Falentino, 2019), (Shofwani & Hariyadi, 2019) and (Asmayana, 2018) compensation has a role in increasing the achievement capacity of its employees and the performance of the company. Employee performance will improve if workers are satisfied with the compensation distributed.…”
Section: Introductionmentioning
confidence: 99%